1991
DOI: 10.1159/000200753
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A<sub>2</sub> Activity of Colonic Mucosa in Patients with Ulcerative Colitis

Abstract: Activation of enzyme phospholipase A2 (EC 3.1.1.4), the major liberator of arachidonic acid, has been proposed as a component in the pathogenesis of inflammatory bowel disease. To test the hypothesis that phospholipase A2 activity is increased in ulcerative colitis, enzyme activity was investigated in colonic biopsies using radiolabelled Escherichia coli as substrate. The study comprised patients with ulcerative colitis (n = 19) and controls without inflammatory bowel disease (n = 7). Ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
(15 reference statements)
0
10
1
Order By: Relevance
“…Previous studies show that the activity of phospholipase A 2 (PLA 2 ) was elevated in patients suffering from IBD. 57,58 It is known that several types of phospholipases exhibit different selectivity for fatty acids at the sn-2 position and for the type of chemical bond at the sn-1 position. Phospholipase A can be found, for example, as a constituent in the membrane of Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that the activity of phospholipase A 2 (PLA 2 ) was elevated in patients suffering from IBD. 57,58 It is known that several types of phospholipases exhibit different selectivity for fatty acids at the sn-2 position and for the type of chemical bond at the sn-1 position. Phospholipase A can be found, for example, as a constituent in the membrane of Gramnegative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis of PC and LPC is of great importance in regulating the permeability of the intestinal epithelium. 57,58 LPC may promote inflammatory effects such as expression of endothelial cell adhesion molecules, growth factors, chemotaxis, and activation of monocytes/macrophages. 59 Since the sums of PC and LPC were likewise diminished in the mucus from UC patients compared to the other 2 groups, a deficit of PC in UC cannot be solely explained by an increase in enzymatic degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Olaison et al 12 demonstrated PLaseA2 activation in the mucosae of CD patients who had experienced a symptomatic ileal recurrence within the previous year. On the other hand, Almer et al 13 found no PLaseA2 activation in UC mucosa. In these studies, PLaseA2 activity was determined by the release of radiolabelled fatty acids from synthetic phosphoglycerides or radiolabelled bacterial cells (E. coli) added to the reaction mixture.…”
Section: Plasea2 Activity In Normal and Inflamed Tissuesmentioning
confidence: 93%
“…It is of interest that metabolism in cellular organelles, such as peroxisomes, was enhanced in CD mucosa, but was suppressed in UC mucosa. Regarding PLaseA2 activity in the mucosa of IBD patients, Olaison et al 12 and Almer et al 13 examined PLaseA2 activity using radiolabelled Escherichia coli as a substrate. Olaison et al 12 demonstrated PLaseA2 activation in the mucosae of CD patients who had experienced a symptomatic ileal recurrence within the previous year.…”
Section: Plasea2 Activity In Normal and Inflamed Tissuesmentioning
confidence: 99%
“…66) High expression of sPLA 2 II in the colon mucosa of patients with Crohn's disease and ulcerative colitis was also reported. 68,69) …”
Section: Does Lpc Exert Gastrointestinal Mucosa-injuring or Protectinmentioning
confidence: 99%